Epiphora before and after upper eyelid functional blepharoplasty: A retrospective cohort study. - Vannakorn Pruksakorn (Public Library of Science (PLoS), 2021)
Epiphora and dermatochalasis are common presentations in the ophthalmology clinic. To evaluate the change of epiphora before and after functional blepharoplasty, this retrospective cohort study reviewed 39 medical records of epiphora patients who underwent upper blepharoplasty. Severity of epiphora using MUNK score was collected and compared between before and at 6 months after blepharoplasty. The analysis model was performed to measure tear breakup time (TBUT) and frequency of artificial tears use. Subgroups of subjects before blepharoplasty to short baseline TBUT (≤ 10 seconds) and long TBUT (≥ 10 seconds) were also evaluated for the MUNK score change. From the analysis of 39 patients, the results showed a statistically significant decrease in post blepharoplasty MUNK score compared to the baseline (all P < 0.001). There was no significant difference between baseline and post-operative TBUT (P > 0.05). Twenty patients were in the short TBUT group and 19 in the long TBUT group. The reduction of MUNK score after blepharoplasty in the short TBUT group was not different to the long TBUT group (P = 0.50, 95% CI -0.84 to 0.41). However, in short TBUT group, frequency of artificial tears use after surgery was less than pre-operation. From the study, upper eyelid blepharoplasty might be one technique reducing the bothersome epiphora in dermatochalasis patients.